A pretreatment method for improving the adhesion of a primer on a steel sheet surface

CN122999486APending Publication Date: 2026-10-30SHANDONG EXPRESSWAY ENGINEERING EQUIPMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611182640.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-05
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,前处理后的钢板依然存在偶发缺陷,导致局部难以被底漆浸润和附着,从而引起底漆的结合力劣化,具有诱发后续腐蚀的高风险

Benefits of technology

通过浸铜处理在钢板表面形成结合力优异的置换铜层,然后根据底漆属性实施匹配的超亲水/超亲油改性处理,在钢板表面形成具有特殊微观形貌的超亲水或超亲油纳米结构,处理过程简单、快速。经过超亲水/超亲油改性后的钢板表面形成具有适中表面粗糙度的微纳米结构,不仅有利于涂装过程中底漆涂料迅速浸润、铺展于钢板表面,增加底漆与钢板的结合效果,而且可以增加机械铆合力,进一步提升底漆展结合力,从而解决普通前处理后底漆对钢板浸润性差、结合力不理想的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999486A_ABST
    Figure CN122999486A_ABST
Patent Text Reader

Abstract

The application discloses a pretreatment method for improving the adhesion of a primer on a steel plate surface, and belongs to the technical field of surface treatment. The method comprises the following steps: using an acid copper immersion liquid containing a soluble cuprous chloride complex to wipe and treat a steel plate, so as to generate a copper deposition layer on the surface of the steel plate; then using the steel plate as an anode, a copper plate as a cathode, and an ultrahydrophilic modification liquid for constant-current electrolysis, so as to form a white film layer with a nanowire structure on the surface of the steel plate, and obtain an ultrahydrophilic surface, which is suitable for the coating of a water-based primer; for an oil-based primer, after ultrahydrophilic modification, further spraying of a fatty acid ethanol solution is performed to carry out ultrahydrophobic modification, so as to form a nanosilk belt structure. According to the method, the surface of the steel plate is adjusted and controlled to have ultrahydrophilic or ultrahydrophobic properties according to the solvent properties of the primer, so that the primer can be fully infiltrated and spread on the surface of the steel plate, and the adhesion between the primer and the steel plate is significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of surface treatment technology, specifically relating to a pretreatment method for improving the adhesion of primer to steel plate surfaces. Background Technology

[0002] The information disclosed in this background section is intended only to enhance understanding of the overall background of the invention and is not necessarily to be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.

[0003] In the field of engineering and manufacturing, steel plates are typically constructed into specialized steel structures through welding or bolting. To extend the lifespan of these steel structures, anti-corrosion treatment is essential. Among the various anti-corrosion solutions for steel structures, applying anti-corrosion coatings is the most common method. The resulting coating effectively blocks corrosive media from contacting the steel substrate, thus preventing corrosion. Typically, the anti-corrosion coating on the steel plate surface is a multi-layered paint film structure, meaning that a primer, intermediate coat, and topcoat are applied sequentially to the steel plate surface. Therefore, ensuring the adhesion between the primer and the steel plate is crucial. Poor adhesion of the primer to the steel plate surface can lead to fatal defects such as peeling, blistering, and flaking of the paint film, directly causing a precipitous decline in the lifespan of the steel structure.

[0004] Typically, oxide scale on the surface of steel plates can weaken the adhesion of paint films, so it is usually necessary to remove the oxide scale before painting. Furthermore, to further improve the adhesion of the primer to the steel plate surface, it is often necessary to increase mechanical bonding force at the interface. For this purpose, special pretreatment is usually performed on the steel plate before applying the primer, such as sandblasting or shot blasting to create a microscopically rough structure, which facilitates the subsequent wetting ability and mechanical adhesion of the primer to the steel plate. However, even after pretreatment, occasional defects may still exist on the steel plate, causing localized areas that are difficult for the primer to wet and adhere to, thus leading to a deterioration in the primer's adhesion and a high risk of inducing subsequent corrosion.

[0005] Therefore, developing a pretreatment method that can effectively improve the adhesion of the primer is crucial for enhancing the corrosion resistance of steel structure engineering. Summary of the Invention

[0006] This invention addresses the shortcomings of existing technologies by providing a pretreatment method to improve the adhesion of primer to steel plate surfaces. This method improves the wettability and adhesion of primer by adjusting the hydrophilicity / oleophilicity of the steel plate to match the properties of the primer.

[0007] To achieve the above objectives, the present invention adopts the following technical solution: A pretreatment method for improving the adhesion of primer to steel plate surface, wherein the primer is a water-based primer or an oil-based primer; When the primer is water-based, pre-treat the steel plate according to the following steps before applying the primer: (1) Copper immersion: Wipe the surface-treated steel plate with copper immersion solution until a copper deposit layer is formed on the surface of the steel plate; (2) Superhydrophilic modification: The steel plate treated in step (1) is used as the anode and the copper plate is used as the cathode. They are separated by a wiping cloth soaked in superhydrophilic modification liquid and electrolyzed with constant current to obtain a white film on the surface of the steel plate. After drying, the pretreatment of the steel plate before coating with water-based primer is completed.

[0008] When the primer is an oil-based primer, the steel plate is pretreated by following steps (1) and (2) before the primer is applied: specifically, the super oleophilic modification liquid is sprayed onto the surface of the steel plate after step (2), and after drying, the pretreatment of the steel plate before the oil-based primer is completed.

[0009] When using water-based primers, the steel plate surface needs to be modified to have superhydrophilic properties and achieve a certain surface roughness, so that the water-based coating can be more easily spread and wetted on the steel plate surface, resulting in better coating adhesion. Through copper immersion and superhydrophilic modification, a nanowire structure is formed on the steel plate surface, thereby achieving a superhydrophilic effect, which is beneficial to the adhesion of the water-based primer.

[0010] When using an oil-based primer, the steel plate needs to be modified from a superhydrophilic surface to a superoleophilic surface, so that the oil-based coating can be more easily spread and wetted on the steel plate surface, thus improving the adhesion of the primer.

[0011] Further, the copper immersion solution in step (1) contains 0.1-0.3 g / L of ascorbic acid, 2.0-3.0 g / L of hydroxyethylidene diphosphonic acid, and 16.3-32.6 g / L of soluble cuprous chloride complex, and the solvent of the copper immersion solution is citric acid solution; the surface treatment is degreasing and derusting.

[0012] Furthermore, the pH of the citric acid solution is 2.1 to 2.3.

[0013] Furthermore, the superhydrophilic modified solution in step (2) contains 3-5 g / L of ascorbic acid, 60-80 g / L of potassium chloride, and 30-35 g / L of soluble cuprous chloride complex.

[0014] Further, the method for preparing the soluble cuprous chloride complex is as follows: a solution containing 0.5-1 mL / L concentrated hydrochloric acid, 1-2 g / L ascorbic acid, 100-120 g / L thiourea, 120-150 g / L potassium chloride, and 44-53 g / L cuprous chloride is heated to 60 °C, stirred for 1 h, filtered while hot, and then cooled to crystallize. The precipitated crystals are dried to obtain the soluble cuprous chloride complex.

[0015] Furthermore, in step (2), the constant current of the constant current electrolysis is 2 to 6 A, and the electrolysis time is 5 to 60 s.

[0016] Further, the superlipophilic modified solution in step (3) is a fatty acid ethanol solution of 1~2 g / L.

[0017] Furthermore, the fatty acid is stearic acid or lauric acid.

[0018] Furthermore, the water-based primer is an inorganic zinc-rich primer, a water-based acrylic coating, or a water-based polyurethane coating.

[0019] Furthermore, the oil-based primer is an epoxy zinc-rich primer or an epoxy micaceous iron oxide coating.

[0020] The beneficial effects of the technical solution provided by this invention are: A copper immersion process creates a highly adhesive copper-substituted layer on the steel plate surface. Then, a matching superhydrophilic / superoleophilic modification treatment is applied based on the primer properties, forming a superhydrophilic or superoleophilic nanostructure with a unique microstructure on the steel plate surface. This process is simple and rapid. The superhydrophilic / superoleophilic modified steel plate surface exhibits a micro / nano structure with moderate surface roughness. This not only facilitates rapid wetting and spreading of the primer during coating, increasing the adhesion between the primer and the steel plate, but also increases mechanical bonding force, further enhancing the primer's adhesion. This solves the problem of poor primer wetting and unsatisfactory adhesion to steel plates after ordinary pretreatment. Attached Figure Description

[0021] Figure 1 This is a scanning electron microscope image of a steel plate after copper immersion in Example 1; Figure 2 The image shows a scanning electron microscope image of the steel plate after superhydrophilic modification in Example 1. Figure 3 This is the instantaneous spread of a 0.05 mL water droplet on the surface of the steel plate after superhydrophilic modification in Example 1. Figure 4 The results of the cross-cut test were performed on the pretreated steel plate of Example 1 after it was coated with an inorganic zinc-rich primer and allowed to dry completely. Figure 5 This is a scanning electron microscope image of the steel plate after superoleophilic modification in Example 2; Figure 6 Example 2: The instantaneous spread of 0.05 mL of toluene dropped onto the surface of a steel plate after superoleophilic modification; Figure 7 The image shows the EDX spectrum of the steel plate after superoleophilic modification in Example 2. Figure 8The results of the cross-cut test were performed on the pretreated steel plate of Example 2 after it was coated with epoxy zinc-rich primer and allowed to dry completely. Figure 9 Images of the areas where the inorganic zinc-rich primer of Comparative Example 1 peeled off after a cross-cut test. Detailed Implementation

[0022] The specific embodiments of the present invention are described in detail below. These embodiments are intended to more fully demonstrate the technical content of the present invention and help to understand the specific implementation process of the present invention, but their content should not be construed as limiting the scope of the claims of the present invention in any way. For those skilled in the art, various adjustments, modifications, and substitutions made to the embodiments without departing from the spirit and scope of the present invention are all within the scope of protection sought by the present invention.

[0023] Example 1 This embodiment provides a pretreatment method for improving the adhesion of primer to steel plate surfaces. When using an inorganic zinc-rich primer, the steel plate is pretreated according to the following steps before applying the primer: (1) Copper immersion: 0.2 g of ascorbic acid, 2.5 g of hydroxyethylidene diphosphonic acid and 16.3 g of soluble cuprous chloride complex were dissolved in 950 mL of citric acid solution with pH 2.3 in sequence. The solution was brought to a final volume of 1000 mL and aged for 24 hours to obtain copper immersion solution. The wiping cloth was soaked in the copper immersion solution and then repeatedly wiped on the steel plate after degreasing and derusting until a copper deposit layer was formed on the surface of the steel plate. (2) Superhydrophilic modification: Connect the steel plate treated in step (1) to the positive terminal of a DC regulated power supply, and connect the copper plate with an area of ​​1 square decimeter to the negative terminal of a DC regulated power supply. The steel plate and the copper plate are separated by a wiping cloth soaked in superhydrophilic modification liquid. Electrolysis is performed at a constant current of 3.5 A for 30 s. A white film layer is obtained on the surface of the steel plate. After drying, the pretreatment of the steel plate is completed before coating with water-based primer. The superhydrophilic modification liquid contains 3.5 g of ascorbic acid, 65 g of potassium chloride and 32 g of the soluble cuprous chloride complex described in step (1) per liter. The preparation method of the soluble cuprous chloride complex in steps (1) and (2) is as follows: a solution containing 1 mL / L concentrated hydrochloric acid, 1 g / L ascorbic acid, 100 g / L thiourea, 120 g / L potassium chloride and 44 g / L cuprous chloride is heated to 60 °C, stirred for 1 hour, filtered while hot and then cooled to crystallize. The precipitated crystals are dried to obtain the soluble cuprous chloride complex.

[0024] In step (1) of this embodiment, the copper immersion solution contains a low concentration of soluble cuprous chloride complex, which is a triligand complex formed by cuprous chloride and thiourea, providing stable cuprous ions and their coordinating agents. Citric acid and hydroxyethylidene diphosphonic acid in the copper immersion solution not only act as auxiliary coordinating agents for cuprous ions but also provide an acidic environment, which is beneficial for the stability of thiourea and the active dissolution of the steel plate. The trace amount of ascorbic acid in the copper immersion solution acts as an antioxidant, preventing the oxidation of thiourea and cuprous ions. In addition, hydroxyethylidene diphosphonic acid can also prevent over-corrosion of the steel plate. Therefore, when the wiping cloth is soaked in the copper immersion solution and the steel plate is repeatedly wiped, a copper-iron substitution reaction occurs on the surface of the steel plate. Under the activation of citric acid and hydroxyethylidene diphosphonic acid, the cuprous ions are reduced and a copper deposition layer is generated, the microstructure of which is as follows: Figure 1 As shown. More importantly, due to the large amount of cuprous ion ligands in the copper immersion solution, the copper deposition layer exhibits excellent adhesion.

[0025] In step (2), since the superhydrophilic modified solution contains thiourea and chloride ions, ascorbic acid can ensure the stability of the electrolysis system during high-current constant-current electrolysis. Meanwhile, the copper on the steel plate surface, acting as the anode, can be rapidly oxidized to produce monovalent copper, and under the influence of a large number of chloride ions, it utilizes the common ion effect to generate an insoluble cuprous chloride structure with a nanowire structure, the microstructure of which is as follows: Figure 2 As shown, it appears as a uniform white film. When a white cuprous chloride film forms on the steel plate surface, its nanowire structure exhibits excellent hydrophilic properties; when a water droplet is placed on its surface, it spreads rapidly, as... Figure 3 As shown. Therefore, after pretreatment, the inorganic zinc-rich coating can be sprayed onto the steel plate surface quickly and effectively. The nanowire structure on the steel plate surface further enhances the mechanical adhesion of the inorganic zinc-rich coating. After one coat of primer is applied and fully dried, the film thickness is 40 micrometers. The adhesion was measured using the cross-cut test, and the results are as follows. Figure 4 As shown, no primer peeled off after the test, proving that the water-based primer has excellent adhesion to the surface of the steel plate after pretreatment.

[0026] Example 2 This embodiment provides a pretreatment method to improve the adhesion of primer to steel plate surface. When using epoxy zinc-rich primer, before applying primer, the steel plate is treated sequentially according to steps (1) and (2) of Example 1, and then superoleophilic modification is performed: 1.5 g / L stearic acid ethanol solution is sprayed onto the steel plate surface, and after natural drying, the spraying is repeated twice. After drying, the steel plate pretreatment is completed.

[0027] In the superoleophilic modification process, stearic acid ethanol solution is sprayed onto the surface of the steel plate after step (2) treatment, changing the original nanowire structure and forming a structure like... Figure 5 The nanoribbon structure is shown. Energy dispersive spectroscopy (EDS) was performed on the formed nanoribbon structure to analyze its composition, and the results are as follows: Figure 7 As shown, the nanoribbon structure contains a large amount of carbon, exceeding 75% atomically, while chlorine and copper account for 5.19% and 6.17% atomically, respectively. This indicates that stearic acid molecules embed within the original cuprous chloride, altering the original nanowire structure and forming a nanoribbon structure. Because stearic acid molecules are lipophilic, the steel plate modified with superlipophilic treatment not only exhibits microscopic roughness but also superlipophilic properties; when toluene is dropped onto its surface, it spreads rapidly, as shown... Figure 6 As shown. Therefore, after pretreatment, the epoxy zinc-rich primer can spread rapidly and excellently on the steel plate surface. The nanoribbon structure on the steel plate surface helps to further improve the mechanical adhesion of the epoxy zinc-rich primer. After one coat of primer is applied and fully dried, the film thickness is 40 micrometers. The adhesion was measured using the cross-cut test, and the results are as follows. Figure 8 As shown, no primer peeled off after the test, proving that the epoxy zinc-rich primer has excellent adhesion to the surface of the steel plate after pretreatment.

[0028] Example 3 This embodiment describes a pretreatment method to improve the adhesion of primer to steel plate surfaces. When using an inorganic zinc-rich primer, the difference from Example 1 lies in step (1): 0.1 g of ascorbic acid, 3.0 g of hydroxyethylidene diphosphonic acid, and 32.6 g of a soluble cuprous chloride complex are sequentially dissolved in 950 mL of citric acid solution with a pH of 2.1. After adjusting the volume to 1000 mL, the solution is aged for 24 hours to obtain a copper-immersing solution. A wiping cloth is soaked in the copper-immersing solution and repeatedly wiped on the degreased and derusted steel plate until a copper deposition layer is formed on the steel plate surface. The remaining steps are the same as in Example 1.

[0029] Example 4 This embodiment provides a pretreatment method to improve the adhesion of primer to steel plate surfaces. When using water-based acrylic coating, the difference from Example 1 lies in step (1): 0.3 g of ascorbic acid, 2.0 g of hydroxyethylidene diphosphonic acid, and 24.5 g of soluble cuprous chloride complex are sequentially dissolved in 950 mL of citric acid solution with a pH of 2.2. After adjusting the volume to 1000 mL, the solution is aged for 24 hours to obtain a copper-impregnating solution. The wiping cloth is then soaked in the copper-impregnating solution and repeatedly wiped on the degreased and derusted steel plate until a copper deposition layer is formed on the steel plate surface. The remaining steps are the same as in Example 1.

[0030] Example 5 This embodiment provides a pretreatment method to improve the adhesion of primer to steel plate surfaces. When using water-based polyurethane coating, the difference from Embodiment 1 lies in step (2): the steel plate treated in step (1) is connected to the positive terminal of a DC regulated power supply, and a copper plate with an area of ​​1 square decimeter is connected to the negative terminal of the DC regulated power supply. The steel plate and the copper plate are separated by a wiping cloth soaked in a superhydrophilic modifying liquid. A constant current electrolysis of 2 A is performed for 60 s, resulting in a white film layer on the steel plate surface. After drying, the pretreatment of the steel plate before coating with water-based primer is completed. The superhydrophilic modifying liquid contains 5 g of ascorbic acid, 80 g of potassium chloride, and 35 g of soluble cuprous chloride complex per liter. The remaining steps are the same as in Embodiment 1.

[0031] Example 6 This embodiment provides a pretreatment method to improve the adhesion of primer to steel plate surfaces. When using an inorganic zinc-rich primer, the difference from Embodiment 1 lies in step (2): the steel plate treated in step (1) is connected to the positive terminal of a DC regulated power supply, and a copper plate with an area of ​​1 square decimeter is connected to the negative terminal of the DC regulated power supply. The steel plate and the copper plate are separated by a wiping cloth soaked in a superhydrophilic modifying liquid. A constant current electrolysis of 6 A is performed for 5 s, resulting in a white film layer on the steel plate surface. After drying, the pretreatment of the steel plate before coating with a water-based primer is completed. The superhydrophilic modifying liquid contains 3 g of ascorbic acid, 60 g of potassium chloride, and 30 g of soluble cuprous chloride complex per liter. The remaining steps are the same as in Embodiment 1.

[0032] Example 7 This embodiment provides a pretreatment method to improve the adhesion of primer to steel plate surfaces. When using an inorganic zinc-rich primer, the difference from Example 1 lies in the preparation method of the soluble cuprous chloride complex: a solution containing 0.5 mL / L concentrated hydrochloric acid, 2 g / L ascorbic acid, 120 g / L thiourea, 150 g / L potassium chloride, and 53 g / L cuprous chloride is heated to 60°C, stirred for 1 hour, filtered while hot, and then cooled for crystallization. The precipitated crystals are dried to obtain the soluble cuprous chloride complex. The remaining steps are the same as in Example 1.

[0033] Example 8 This embodiment provides a pretreatment method to improve the adhesion of primer to steel plate surfaces. When using an inorganic zinc-rich primer, the difference from Example 1 lies in the preparation method of the soluble cuprous chloride complex: a solution containing 0.8 mL / L concentrated hydrochloric acid, 1.6 g / L ascorbic acid, 110 g / L thiourea, 135 g / L potassium chloride, and 49 g / L cuprous chloride is heated to 60°C, stirred for 1 hour, filtered while hot, and then cooled for crystallization. The precipitated crystals are dried to obtain the soluble cuprous chloride complex. The remaining steps are the same as in Example 1.

[0034] Example 9 This embodiment provides a pretreatment method to improve the adhesion of primer to steel plate surfaces. When using epoxy micaceous iron oxide coating, the difference from Embodiment 2 lies in the superoleophilic modification: a 1 g / L stearic acid ethanol solution is sprayed onto the steel plate surface, allowed to dry naturally, and then sprayed twice more. After drying, the steel plate pretreatment is complete. The remaining steps are the same as in Embodiment 2.

[0035] Example 10 This embodiment provides a pretreatment method to improve the adhesion of primer to the surface of steel plate. When using epoxy zinc-rich coating, the difference from Example 2 is the superoleophilic modification: a 2 g / L lauric acid ethanol solution is sprayed onto the surface of the steel plate, and after natural drying, the spraying is repeated twice. After drying, the pretreatment of the steel plate is completed.

[0036] Comparative Example 1 The difference from Example 1 is that when using an inorganic zinc-rich primer, only degreasing and rust removal are performed before coating. Images of areas where the paint film peeled off were obtained from a cross-cut test after the primer had fully dried, as shown in the image. Figure 9 As shown, 11 squares (i.e., 11%) of the areas where the paint film has peeled off have either peeled off or bulged at the cut.

[0037] Comparative Example 2 The difference from Example 2 is that when using an epoxy zinc-rich primer, only degreasing and rust removal are performed before coating.

[0038] Comparative Example 3 The difference from Example 4 is that when using water-based acrylic paint, only degreasing and rust removal are performed before applying the primer.

[0039] Comparative Example 4 The difference from Example 5 is that when using water-based polyurethane coatings, only degreasing and rust removal are performed before applying the primer.

[0040] Comparative Example 5 The difference from Example 9 is that when using epoxy micaceous iron oxide coating, only degreasing and derusting are performed before applying the primer.

[0041] After the steel plates of Examples 1-10 and Comparative Examples 1-5 were coated with primer and allowed to dry, the adhesion of the primer was evaluated using the cross-cut test. According to the national standard GB / T9286 for paint film adhesion, the steel plates pretreated in Examples 1-10 showed no coating peeling after primer application and the cross-cut test, with an adhesion grade of 0. The steel plates of Comparative Examples 1 and 5 showed an adhesion grade of 2 after primer application and the cross-cut test. The steel plates of Comparative Examples 2, 3, and 4 showed an adhesion grade of 1 after primer application and the cross-cut test. The adhesion test results demonstrate that this invention can effectively improve the adhesion of the primer to the steel plate surface by controlling the surface properties of the steel plate through pretreatment, based on the characteristics of different primers.

[0042] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A pretreatment method for improving the adhesion of primer to steel plate surfaces, characterized in that, The primer is either a water-based primer or an oil-based primer; When the primer is water-based, pre-treat the steel plate according to the following steps before applying the primer: (1) Copper immersion: Wipe the surface-treated steel plate with copper immersion solution until a copper deposit layer is formed on the surface of the steel plate; (2) Superhydrophilic modification: The steel plate treated in step (1) is used as the anode and the copper plate is used as the cathode. They are separated by a wiping cloth soaked in superhydrophilic modification liquid and electrolyzed with constant current to obtain a white film on the surface of the steel plate. After drying, the pretreatment of the steel plate before coating with water-based primer is completed. When the primer is an oil-based primer, the steel plate is pretreated by following steps (1) and (2) in sequence before applying the primer. Specifically, the super oleophilic modification liquid is sprayed onto the surface of the steel plate after step (2) and dried to complete the pretreatment of the steel plate before applying the oil-based primer.

2. The pretreatment method according to claim 1, characterized in that, The copper immersion solution in step (1) contains 0.1-0.3 g / L of ascorbic acid, 2.0-3.0 g / L of hydroxyethylidene diphosphonic acid, and 16.3-32.6 g / L of soluble cuprous chloride complex. The solvent for the copper immersion solution is citric acid solution. The surface treatment is degreasing and derusting.

3. The pretreatment method according to claim 2, characterized in that, The pH of the citric acid solution is 2.1 to 2.

3.

4. The pretreatment method according to claim 1, characterized in that, The superhydrophilic modified solution in step (2) contains 3-5 g / L of ascorbic acid, 60-80 g / L of potassium chloride, and 30-35 g / L of soluble cuprous chloride complex.

5. The pretreatment method according to claim 2 or 4, characterized in that, The method for preparing the soluble cuprous chloride complex is as follows: a solution containing 0.5-1 mL / L concentrated hydrochloric acid, 1-2 g / L ascorbic acid, 100-120 g / L thiourea, 120-150 g / L potassium chloride, and 44-53 g / L cuprous chloride is heated to 60 °C, stirred for 1 h, filtered while hot, and then cooled to crystallize. The precipitated crystals are dried to obtain the soluble cuprous chloride complex.

6. The pretreatment method according to claim 1, characterized in that, The constant current for constant current electrolysis in step (2) is 2 to 6 A, and the electrolysis time is 5 to 60 s.

7. The pretreatment method according to claim 1, characterized in that, The superlipophilic modification solution is a fatty acid ethanol solution of 1~2 g / L.

8. The pretreatment method according to claim 7, characterized in that, The fatty acid mentioned is stearic acid or lauric acid.

9. The pretreatment method according to claim 1, characterized in that, The water-based primer is an inorganic zinc-rich primer, a water-based acrylic coating, or a water-based polyurethane coating.

10. The preprocessing method according to claim 1, characterized in that, The oil-based primer is an epoxy zinc-rich primer or an epoxy micaceous iron oxide coating.